SiO2@LaOF:Eu3+ in white light emitting diodes optic efficiency enhancement - Phuc Dang Huu; Guo Feng Luo; Minh Pham Quang (Bulletin of Electrical Engineering and Informatics, 2022)
The earliest intense red hue compound of SiO2@LaOF:Eu3+ core-shell nanostructures (NS) was created utilizing a basic solvothermal technique and heat processing. The produced core-shell particles are spherical, non-agglomerated, and have restricted size dispersion. Photoluminescence (PL) radiation spectra exhibit sharp maximums in 593, 611, and 650 nm, corresponding with 5D0 -- more than 7FJ (J=0, 1, 2) Eu3+ conversions. The Judd-Ofelt (J-O) hypothesis helps determine the spectrum strength indices and Eu-O ligand activities. The CIE coordinates are x=0.63, y=0.36, nearly equal the NTSC coordinates which are x=0.67, y=0.33. Because of the CCT level of 3475 K, which is lower than 5000 K, this phosphor is appropriate for warm light-emitting diodes. To visualize latent fingermarks both porous and non-porous substrates, the fluorescent labeling marker adapted core-cover SiO2 (coat III)@LaOF:Eu3+ (5 mol%) was utilized. With no background influence, the fingermarks obtained are exceedingly sensible and exclusive, permitting for fingerprint ridge features ranging from level-I to level-III. The findings indicate the significant enhancement in the illumination of corecover NS as a responsive operational nanoparticle for increased forensics and firm status illuminating implementations.